Bakti Sosial Pemeriksaan Gratis Relawan Medis Beriuk Bareng Peduli di Desa Poton Bako Kecamatan Jerowaru, Kabupaten Lombok Timur - M Ari Wisnu; Lalu Sanik Wahyu Fadil Amrulloh; Siti Amalia Wahyu Pratiwi; Widayanti Supraba; Gilang Pratama Putra; Ika Wahyuni; Zurhainun Mutmainnah; Hendriawan Hendriawan (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2026)
This community service activity was conducted in Poton Bako Village, Jerowaru District, where limited access to health services and low public awareness of routine health check-ups were identified. The activity aimed to improve access to healthcare services and promote early disease detection. A descriptive observational approach was used through a free health screening program involving 50 participants aged 3 to 45 years. The implementation included registration, vital signs examination, basic laboratory tests, medical examination by a general practitioner, as well as medication dispensing and education on proper drug use. The results showed that participants obtained initial information about their health conditions and demonstrated increased awareness of the importance of regular health check-ups. The activity also supported preventive efforts through health education and appropriate medication use. It was concluded that free health screening was effective in improving access to healthcare services and increasing community awareness of early disease detection.